A Hidden Markov Model for Pedestrian Navigation - Seitz, Jochen; Vaupel, Thorsten; Meyer, Steffen; Gutierrez, Javier; Thielecke, Jörn (IEEE Xplore, 2010)
We present an algorithm for pedestrian navigation optimized for smart mobile platforms using the present low-cost sensors and the limited processing power. The algorithm is based on a Hidden Markov Model that combines Wi-Fi positioning and dead reckoning. The hidden states are the positions of the Wi-Fi fingerprints in the database. The state transition includes dead reckoning based on step length estimation from acceleration measurements and compass heading calculated from magnetic field measurements. In the measurement update a database correlation of the actual Wi-Fi signal strength measurements with the stored values in the fingerprints has been performed. In simulations and tests we demonstrate that in this way ambiguities common in Wi-Fi positioning can be reduced. Therefor, higher accuracy and robustness can be achieved. © 2010 IEEE.
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.20107t
Keywords: Dead Reckoning; Hidden Markov Models; Pedestrian Navigation; Positioning; Wireless LAN

A Hidden Markov Model for Urban Navigation Based on Fingerprinting and Pedestrian Dead Reckoning - Thielecke, Jörn; Gutiérrez Boronat, Javier; Seitz, Jochen; Meyer, Steffen; Jahn, Jasper; Vaupel, Thorsten (IEEE Xplore, 2010)
An algorithm for pedestrian navigation in indoor and urban canyon environments is presented. It considers platforms with low processing power and low-cost sensors. A combination of Wi-Fi positioning and dead reckoning, based on a Hidden Markov Model, is used. The positions of the Wi-Fi fingerprints in the database are used as hidden states. Dead reckoning is taken for state transition and a database correlation of the Wi-Fi signal strength measurements is performed in the measurement update. The dead reckoning consists of an accelerometer driven step length estimation and a magnetic field based heading calculation. Simulations and tests demonstrate that in this way ambiguities common in Wi-Fi positioning can be solved and outages can be bridged. Therefore, higher accuracy and robustness can be achieved.
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.ahidde
Keywords: Dead Reckoning; Hidden Markov Models; Pedestrian Navigation; Positioning; Wireless LAN

A particle filter for Wi-Fi azimuth and position tracking with pedestrian dead reckoning - Thielecke, Jörn; Vaupel, Thorsten; Seitz, Jochen (8th Workshop on Sensor Data Fusion: Trends, Solutions, Applications, SDF 2013, 2013)
A tracking algorithm for estimating the azimuth angle regarding north and a two-dimensional position of a mobile unit carried by a pedestrian is presented. Using Wi-Fi signal strength measurements the position of a mobile receiver can be estimated using so called fingerprinting methods. If the signal strengths measurements are collected with directional antennas additionally the azimuth can be estimated. For sensor data fusion of Wi-Fi signal strength measurements, acceleration measurements and angular rate measurements a particle filter is presented. The well known Wi-Fi fingerprinting approach is used to calculate the particle weights and pedestrian dead reckoning to sample the particles. Measurements have been collected inside and outside of an office building to evaluate the performance. Including step detection based on acceleration measurements reduces mainly the positioning error, including angular rate measurements reduces mainly the azimuth estimation error. Electronic compasses, which are susceptible to faults, are not needed to estimate the azimuth indoors. Especially in indoor environments this approach facilitates the use of electronic guides that offer additional information by means of augmented reality, e.g. on museum exhibits in visual range. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.aparti

Comparison and evaluation of acceleration based step length estimators for handheld devices - Patino-Studencki, Lucila; Batzer, Ulrich; Gutiérrez Boronat, Javier; Jahn, Jasper; Seitz, Jochen (2010 International Conference on Indoor Positioning and Indoor Navigation, 2010)
A comparison between different step length estimation algorithms for pedestrian dead reckoning is presented. This work covers theoretic evaluation of the estimators' performance and presents a comparison based on measurement data. Measurement data were taken from a group of five adults walking at three different velocities. For reference, the sensors were placed according to the recommendation given for each algorithm. In respect to everyday usability the performance of the estimators is furthermore evaluated for arbitrary placement of the sensors, as it is the case when using a mobile measurement platform like a smartphone.
Keywords: Global Positioning System; inertial navigation; length measurement; mobile handsets; mobile radio; notebook computers; sensor placement; acceleration; handheld devices; mobile measurement; pedestrian dead reckoning; sensor placement; smartphone; step length estimators; Acceleration; Accelerometers; Calibration; Estimation; Legged locomotion; Sensors; Systematics; Accelerometer; Pedestrian Dead Reckoning; Pedestrian Navigation; Step Length Estimation

Sensor Data Fusion for Pedestrian Navigation Using WLAN and INS - Seitz, Jochen; Patino-Studencki, Lucila; Schindler, Bernd; Haimerl, Stephan; Gutierrez, Javier; Meyer, Steffen; Thielecke, Jörn (Symposium Gyro Technology 2007, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.komele.sensor

Sensor Data Fusion for Seamless Navigation using Wi-Fi Signal Strengths and GNSS Pseudoranges - Thielecke, Jörn; Gutiérrez Boronat, Javier; Patino-Studencki, Lucila; Seitz, Jochen; Richter, Philipp (Proceedings of the European Navigation Conference 2012, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.sensor

Spatial interpolation of Wi-Fi RSS fingerprints using model-based universal kriging - Kram, Sebastian; Nickel, Christian; Seitz, Jochen; Patino-Studencki, Lucila; Thielecke, Jörn (2017 Symposium on Sensor Data Fusion: Trends, Solutions, Applications, SDF 2017, 2017)

UWB Feature Localization for Imaging - Seitz, Jochen; Schaub, Markus; Hirsch, Ole; Zetik, Rudolf; Deißler, Tobias; Thomä, Reiner; Thielecke, Jörn (UWB Feature Localization for Imaging, 2008)
Object recognition, localization and imaging capabilities of ultra-wideband signals are demonstrated in this contribution. Resembling a bat, the experimental setup comprises one transmitter and two receivers. Instead of ultrasound, electromagnetic ultra-wideband (UWB) signals are used to recognize and localize features of the surroundings like e.g. walls, edges or corners. Each feature corresponds to a hypothesis on the dominant reflection and scattering conditions described in terms of simple ray-tracing relationships. The hypothesis matching best the propagation time measurements is picked to identify and localize the feature in front of the moving UWB bat. Henceforth these features could be used as landmarks for bat navigation. Both, position and attitude of the UWB bat could be continuously updated based on a map of landmarks. This kind of navigation is well-known in the literature as simultaneous localization and mapping. Since position and attitude of the UWB bat are tracked, an image of the vicinity in front of the UWB bat can be compiled by superimposing the impulse responses recorded at the various locations. This contribution describes the pivotal elements to this approach: feature recognition and localization as well as bat-type imaging. ©2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.komele.uwbfea
Keywords: Feature extraction; Imaging; Localization; Ultra wide band

Wi-Fi Attitude and Position Tracking - Thielecke, Jörn; Seitz, Jochen; Vaupel, Thorsten; Haimerl, Stephan; Meyer, Steffen; Gutiérrez Boronat, Javier; Rohmer, Günter (Microelectronic Systems: Circuits, Systems and Applications, 2012)
UnivIS-Import:2015-04-20:Pub.2012.tech.IE.komele.wifiat
Keywords: Positioning; Navigation; Wireless LAN

Wi-Fi azimuth and position tracking: Signal propagation, modeling and evaluation - Thielecke, Jörn; Vaupel, Thorsten; Seitz, Jochen (Proceedings 16th International Conference on Information Fusion, FUSION 2013, 2013)
Tracking algorithms for estimating and tracking the azimuth angle regarding north and a two-dimensional position of a mobile unit carried by a pedestrian are presented. Outdoors, the azimuth angle of a device can be easily detected using an electronic compass. The position can be calculated using a global navigation satellite system. Indoors, magnetic disturbances lead to unreliable compass outputs. Also, indoors there exists no standard positioning system. Using Wi-Fi signal strength measurements the position of a receiver can be tracked using so called fingerprinting methods. If the signal strengths measurements are collected with directional antennas additionally the azimuth can be tracked. For the presented tracking filters we extended Wi-Fi based Markov localization algorithms for evaluating directional antennas to calculate azimuth besides position. Furthermore, these techniques have been adapted to use a particle filter for the estimation. Well known Wi-Fi fingerprinting approaches are included in the measurement models and pedestrian dead reckoning in the prediction models. Measurements have been collected inside and outside of an office building to evaluate the performance of the different tracking algorithms. Especially in indoor environments these approaches facilitate the use of electronic guides that offer additional information by means of augmented reality, e.g. on museum exhibits in visual range. © 2013 ISIF ( Intl Society of Information Fusi.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.wifiaz

Wi-Fi Azimuth and Position Tracking Using Directional Received Signal Strength Measurements - Seitz, Jochen; Vaupel, Thorsten; Haimerl, Stephan; Gutiérrez Boronat, Javier; Thielecke, Jörn (2012 Workshop on Sensor Data Fusion: Trends, Solutions, Applications (SDF), 2012)
A new approach for estimating and tracking the azimuth angle regarding north and a two-dimensional position of a mobile unit is presented. Outdoors, the azimuth angle of a device can be easily detected using an electronic compass and the position can be calculated using a global navigation satellite system (GNSS). Indoors, magnetic disturbances lead to unreliable compass outputs. Also, indoors there exists no standard positioning system like GNSS outdoors. The presented approach is based on Wi-Fi signal strength measurements collected by four horizontally arranged directional antennas. To proof the concept the well known Wi-Fi fingerprinting based on the normalized Euclidean distance in signal space has been adopted. A test with measurements collected in a laboratory demonstrates the feasibility of the approach. Especially in indoor environments this facilitates the use of electronic guides that offer additional information by means of augmented reality, e.g. on museum exhibits in visual range. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.wifiaz

Wi-Fi positioning: System considerations and device calibration - Thielecke, Jörn; Haimerl, Stephan; Kiefer, Frédéric; Vaupel, Thorsten; Seitz, Jochen (IEEE Xplore, 2010)
Due to an increasing number of public and private access points in indoor and urban environments, Wi-Fi positioning becomes more and more attractive for pedestrian navigation. In the last ten years different approaches and solutions have been developed. But Wi-Fi hardware and network protocols have not been designed for positioning. Therefore, Wi-Fi devices have different hardware characteristics that lead to different positioning accuracies. In this article we analyze and discuss hardware characteristics of Wi-Fi devices with a focus on the so called Wi-Fi fingerprinting technique for positioning. The analysis is based on measurements collected using a static setup in an anechoic chamber to minimize signal reflections and noise. Characteristics like measurement offsets and practical polling intervals of different mobile devices have been examined. Based on this analysis a calibration approach to compensate the measurement offsets of Wi-Fi devices is proposed. Experimental results in a typically office building are presented to evaluate the improvement in localization accuracy using the calibration approach. © 2010 IEEE.
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.wifipo
Keywords: Positioning; Wireless LAN; System Analysis; Error Analysis; Calibration